(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
Car (or Car-Nicobarese) is the most widely spoken of the Nicobaric languages, which belong to the Austro-Asiatic family. Car-Nicobarese word order has been described as basically VOS. This short article attempts to offer a description of some features of this language (basic syntax, the use of certain affixes, some lexical facts…) on the basis of the Bible in Car. Some interesting translation problems are mentioned too, especially where there is no precise Car word corresponding to the Greek original. KEYWORDS: Car (or Car-Nicobarese), VOS languages, classifiers, spatial relations, translation